Diagnostic point‐of‐care ultrasound for hospitalists. Issue 2 (19th November 2014) - Soni, Nilam J.; Lucas, Brian P.
<x xml:space="preserve">Abstract</x> We review the literature on diagnostic point‐of‐care ultrasound applications most relevant to hospital medicine and highlight gaps in the evidence base. Diagnostic point‐of‐care applications most relevant to hospitalists include cardiac ultrasound for left ventricular systolic function, pericardial effusion, and severe mitral regurgitation; lung ultrasound for pneumonia, pleural effusion, pneumothorax, and pulmonary edema; abdominal ultrasound for ascites, aortic aneurysm, and hydronephrosis; and venous ultrasound for central venous volume assessment and lower extremity deep venous thrombosis. Hospitalists and other frontline providers, as well as physician trainees at various levels of training, have moderate to excellent diagnostic accuracy after brief training programs for most of these applications. Despite the evidence supporting the diagnostic accuracy of point‐of‐care ultrasound, experimental evidence supporting its clinical use by hospitalists is limited to cardiac ultrasound. Journal of Hospital Medicine 2015;10:120–124. © 2014 Society of Hospital Medicine